Conférence de Ferdulis Zita Odome Angone, enseignante chercheure à l’UCAD au Sénégal (2022)
Ferdulis Zita Odome Angone, enseignante chercheure à l’UCAD au Sénégal et autrice du livre « Femmes noires francophones: Une réflexion sur le patriarcat et le racisme aux XX-XXIe siècles » était présente dans le cours FEM-7000-31, le 12 octobre 2022, afin d’échanger avec les personnes étudiantes et le public.
Keywords: 1900-1999; 2000 à aujourd'hui; approches et analyses; cours; cycles supérieurs; discipline; fem7000; femmes* africaines; féminisme décolonial; géographie; histoire; histoire des femmes*; intersectionnalité; patriarcat; périodes historiques; racisme; sciences humaines; systèmes d'oppressions

#MeToo and testimonial injustice: An investigation of moral and conceptual knowledge - Hänel, Hilkje C (Philosophy & Social Criticism, 2022)
Two decades ago, Tarana Burke started using the phrase ‘me too’ to release victims of sexual abuse and rape from their shame and to empower girls from minority communities. In 2017, actress Alyssa Milano made the hashtag #MeToo go viral. This article’s concern is with the role of testimonial practices in the context of sexual violence. While many feminists have claimed that the word of those who claim to being sexually violated by others (should) have political and/or epistemic priority, others have failed to recognize the harm and injury of instances of sexual violence that are not yet acknowledged as such and failed to listen to victims from marginalized social groups. In fact, some feminists have attacked #MeToo for mingling accounts of ‘proper’ sexual violence and accounts that are not ‘proper’ experiences of sexual violence. My aim in this article is to show why this critique is problematic and find a philosophically fruitful way to understand the #MeToo-movement as a movement that strives for moral and conceptual progress.
Keywords: #metoo; approches et analyses; cours; cycles supérieurs; discipline; fem9000; justice sociale; patriarcat; philosophie; racisme; sciences humaines; sexisme; systèmes d'oppressions; thématiques; violences; violences sexistes et sexuelles; violences sexuelles

Indigenous parents and child welfare: Mistrust, epistemic injustice, and training - Leckey, Robert; Schmieder-Gropen, Raphael; Nnebe, Chukwubuikem; Clouthier, Miriam (Social & Legal Studies, 2022)
The settler state's taking of Indigenous children into care disrupts their communities and continues destructive, assimilationist policies. This article presents the perceptions of lawyers, social workers and judges of how Indigenous parents experience child welfare in Quebec. Our participants characterized those experiences negatively. Barriers of language and culture as well as mistrust impede meaningful participation. Parents experience epistemic injustice, wronged in their capacity as knowers. Mistrust also hampers efforts to include Indigenous workers in the system. Emphasizing state workers’ ignorance of Indigenous family practices and the harms of settler colonialism, participants called for greater training. But critical literature on professional education signals the limits of such training to change institutions. Our findings reinforce the jurisdictional calls away from improving the system towards empowering Indigenous peoples to run services of child welfare. The patterns detected and theoretical resources used are relevant to researchers of other institutions that interact with vulnerable populations.
Keywords: 2000 à aujourd'hui; 2020-2029; amériques; approches et analyses; australie; canada; care; cours; cycles supérieurs; discipline; droit; enfants autochtones; fem9000; injustice; inégalités; nouvelle-zélande; océanie; politique assimilationniste; périodes historiques; racisme; régions géographiques; santé; science politique et droit; sciences humaines; sciences sociales; système colonial; systèmes d'oppressions; thématiques; violences; états coloniaux

Microaggressions and philosophy - Freeman, Lauren; Weekes Schroer, Jeanine (Routledge, 2020)
"This is one of the first books to offer a comprehensive philosophical treatment of microaggressions. Its aims are to provide an intersectional analysis of microaggressions that cuts across multiple groups and dimensions of oppression and marginalization, and to engage a variety of perspectives that have been sidelined within the discipline of philosophy. The volume gathers a diverse group of contributors: philosophers of color, philosophers with disabilities, philosophers of various nationalities and ethnicities, and philosophers of several genders and gender identities. Their unique frames of analysis articulate both how the concept of microaggressions can be used to clarify and sharpen our understanding of subtler aspects of oppression and how analysis, expansion, and reconceiving the notion of a microaggression can deepen and extend its explanatory power. The essays in the volume are divided into four thematic parts. The essays in Part I seek to defend microaggressions from common critiques and to explain their impact beyond the context of college students. In Part II the contributors set forth a framework for legitimizing microaggressions research that takes into account issues of measurement, scale, and replication. Part III explores the harms of microaggressions. The chapters show how small slights can accumulate to produce significant harm at the macro level, demonstrate how microaggressions contribute to epistemic harm, and establish novel understandings of racial and accent-triggered microaggressions. Finally, Part IV addresses issues of disability and ableism within the context of microaggressions. It includes commentary on transgender athletes, disciplinary techniques for bodily nonconformity, ableist exceptionalism, and deafness. Microaggressions and Philosophy features cutting-edge research on an important topic that will appeal to a wide range of students and scholars across disciplines. It includes perspectives from philosophy of psychology, empirically informed philosophy, feminist philosophy, critical race theory, disability theory, philosophy of language, philosophy of science, and social and political philosophy"– Provided by publisher.
Keywords: EDI; approches et analyses; capacitisme; cours; cycles supérieurs; discipline; fem9000; histoire et politique; hétérosexisme; intersectionnalité; inégalités; micro-agression; philosophie; psychologie; racisme; sciences humaines; sexisme; sofia; systèmes d'oppressions; thématiques; transphobie; violences; études critiques de la race; études critiques du handicap